Investigating Brand Awareness, Brand Image, and Perceived Quality on Customer Loyalty - Nadjwa, Antaja; Srivania, Diandra; Mardhiana, Hasna Rizki (Jurnal Vokasi Indonesia, 2024)
This study investigates the impact of brand awareness, brand image, and perceived quality on customer loyalty, with a focus on Telkomsel users within the Creative Business program at Universitas Indonesia. Employing a quantitative research methodology, data were collected from 50 respondents using a structured questionnaire and analyzed using SPSS 26. The findings reveal that all three factors—brand awareness, brand image, and perceived quality—positively influence customer satisfaction, which in turn significantly enhances customer loyalty. Specifically, perceived quality emerged as the most influential factor driving customer satisfaction, followed by brand image and brand awareness. The study underscores the critical role of perceived quality in fostering customer loyalty, suggesting that Telkomsel’s success in retaining customers is largely attributed to its high service standards. This research contributes to the literature on brand management in the telecommunications sector and offers practical insights for enhancing customer loyalty through strategic improvements in brand perception and service quality.